2015
DOI: 10.4236/ojpm.2015.56026
|View full text |Cite
|
Sign up to set email alerts
|

Osteoporosis Health Beliefs, Knowledge and Life Habits among Women in Saudi Arabia

Abstract: Osteoporosis has been recognized as a major public health problem by healthcare providers in Saudi Arabia. The present study examines the osteoporosis knowledge, health beliefs, and some of the life habits in two different Saudi women's groups (with family history, and without family history), to find the association of their knowledge and health beliefs with their preventive practice. This is a descriptive cross-sectional study conducted among a convenience sample of 288 young age (20 to 40 years) women atten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 41 publications
1
6
0
Order By: Relevance
“…Even if Saudi Arabia is considered a sunny country, we found that about 60% of the total population did not expose themselves to sunlight, with even higher percentages reaching as much as 70% among the osteopenic-osteoporotic group. Similar findings have been reported in previous studies 7,14 . This low rate of exposure to sunlight has been justified by lack of awareness, hot climate and limited out-door activities.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Even if Saudi Arabia is considered a sunny country, we found that about 60% of the total population did not expose themselves to sunlight, with even higher percentages reaching as much as 70% among the osteopenic-osteoporotic group. Similar findings have been reported in previous studies 7,14 . This low rate of exposure to sunlight has been justified by lack of awareness, hot climate and limited out-door activities.…”
Section: Discussionsupporting
confidence: 93%
“…This means that adopting healthy lifestyles such as adequate diet, sun exposure and exercising might help prevent the development and progress of osteopenia and osteoporosis. Alotaibi et al 7 indicated that the first step in the prevention of osteoporosis in women should take the first step of creating an awareness among them about the risk factors of this disease. Such awareness can only be achieved by the understanding of the underlying factors leading to osteopenia and osteoporosis among this population 7 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to health promotion movements initiated by the WHO Ottawa Charter in the mid-1980s, have become major pillars of health promotion reform worldwide and the WHO set a goal to increase the number of females trained regarding osteoporosis prevention. Several studies have also shown positive impacts of HBM on modifying health behaviors (Al-Otaibi, 2015;Edmonds et al, 2012;Elsabagh et al, 2015;Evenson & Sanders, 2016;Sanaeinasab et al, 2014). In our country, no studies were found that examined the effects of education program on knowledge, preventive behaviors, beliefs, and clinical outcomes of women aged 18 to 49 years old toward osteoporosis.…”
Section: Introductionmentioning
confidence: 84%
“…SF = Survey Form; ORES = Osteoporosis Risk Estimation Scale; DXA = dual-energy X-ray absorptiometry; OKT = Osteoporosis Knowledge Test; HPEP = health promotion and education program. a performing a BMD examination) and osteoporosis preventive and modifiable behaviors SF-2 (risk reduction behavior such as physical activity and consumption of calcium-rich foods, motivation performing health activities, and sunlight exposure) with combined close and open responses that were gathered from different literatures by the investigators (Al-Otaibi, 2015;Edmonds et al, 2012;Elsabagh et al, 2015;Evenson & Sanders, 2016;Sanaeinasab et al, 2014). In the classification of some of the questions on the SF, some activities like "walking a minimum of 3 times a week for at least 30 min, jogging, swimming, and doing sports" were considered as physical activity (National Osteoporosis Foundation, 2008).…”
Section: Instrumentsmentioning
confidence: 99%